Exposure to the novel insecticide flupyradifurone impairs bumblebee feeding motivation, learning, and memory retention. (15th August 2022) - Siviter, Harry; Muth, Felicity
Abstract: Bees are vital pollinators of crops and wildflowers and as such, wild bee declines threaten food security and functioning ecosystems. One driver of bee declines is the use of systemic insecticides, such as commonly used neonicotinoids. However, rising pest resistance to neonicotinoids, and restrictions on their use in the EU, has increased the demand for replacement insecticides to control crop pests. Flupyradifurone is a novel systemic insecticide that is thought to be relatively 'bee safe' although it can be present in the nectar and pollen of bee-attractive crops. Bumblebees rely on learning to forage efficiently, and thus detriments to learning performance may have downstream consequences on their ability to forage. While neonicotinoids negatively influence bumblebee learning and memory, whether this is also the case for their replacements is unclear. Here, we exposed bumblebees ( Bombus impatiens ) to an acute, field-realistic dose of flupyradifurone before training them to learn either an olfactory or colour association. We found that flupyradifurone impaired bumblebees' learning and memory performance in both olfactory and visual modalities. Flupyradifurone-treated bees were also less motivated to feed. Given the similarity between the detriments to cognition found here and those previously reported for neonicotinoids, this implies that these insecticides may have similar sub-lethal effects on bees. Restrictions on neonicotinoid use are therefore unlikely to benefit bees if novel insecticides like flupyradifurone are used as an alternative, highlighting that current agrochemical risk assessments are not protecting bees from the unwanted consequences of pesticide use. Sub-lethal assessments on non- Apis bees should be made mandatory in agrochemical regulation to ensure that novel insecticides are indeed 'bee safe'. Graphical abstract: Image 1 Highlights: Flupyradifurone is a novel insecticide that could replace neonicotinoids. Flupyradifurone impaired bumblebee olfactory and colour learning. Bumblebees exposed to flupyradifurone were also less motivated to feed. Policy makers should incorporate sub-lethal effects on bumblebees into risk assessment.